Physiological Response of Brachiaria sp on Acid Soil - Achmad Fanindi (Indonesian Center for Animal Research and Development, 2016)
The utilization of marginal land, especially the acid soil, for cultivation of forages is promising. Forage as a source of feed for ruminants, can also be used to improve soil fertility. Brachiaria sp is found widely grow in marginal areas, especially on acid soil showing its high adaptability. The diverse of genotypes have become interesting because the mechanism of its adaption can be studied by observing the physiological response of Brachiaria on acid soil. Brachiaria decumbens has high tolerant, while Brachiaria ruziziensis is sensitive to acid soil. Variance of physiological and morphological responses to acid soil are the foundation for determining the traits of selection in breeding activities of Brachiaria sp. This paper aims to provide the knowledge of physiological response of Brachiaria sp and this information is useful for selection of Brachiaria sp tolerant on acid soil.